2021
DOI: 10.1159/000514564
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Psychotherapy with Neurobiological Methods: Current State and Future Directions

Abstract: <b><i>Background:</i></b> Psychotherapy and pharmacotherapy are first-line treatments for mental disorders. Despite recent improvements, only approximately 50% of the patients reach sustained remission, indicating a need for novel developments. The main concept put forward in this systematic review and hypothesis article is the targeted co-administration of defined neurobiological interventions and specific psychotherapeutic techniques. <b><i>Methods:</i></b> We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In addition, combining neuromodulation with other interventions might engender cumulative or synergistic effects. The choice of interventions would depend on the symptom in question and could include cognitive training (Benedict et al, 2020 ), neurofeedback (Ayache et al, 2021 ), psychotherapies (Sesel et al, 2018 ), physical exercise (Muñoz-Paredes et al, 2022 ), neurobiological methods (Hertenstein et al, 2021 ), interoceptive technologies (Schoeller et al, 2024 ), among others. Finally, coupling neuroimaging and neuromodulation would help unveil the underlying neuromodulation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, combining neuromodulation with other interventions might engender cumulative or synergistic effects. The choice of interventions would depend on the symptom in question and could include cognitive training (Benedict et al, 2020 ), neurofeedback (Ayache et al, 2021 ), psychotherapies (Sesel et al, 2018 ), physical exercise (Muñoz-Paredes et al, 2022 ), neurobiological methods (Hertenstein et al, 2021 ), interoceptive technologies (Schoeller et al, 2024 ), among others. Finally, coupling neuroimaging and neuromodulation would help unveil the underlying neuromodulation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Psychotherapy helps to reconsider one's beliefs and life principles, views and stereotypes, and attitudes towards oneself and others, which also contributes to neuroplasticity activation [13,14]. E. Hertenstein et al [15] highlighted the importance of mindfulness techniques, effectively used in psychotherapy to stimulate brain neuroplasticity through traditional meditation, including attentive listening and accepting the present moment without value judgments. This approach encourages a deep focus on one's thoughts, emotions, and body sensations.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific research has shown that implementing behavioral therapy for individuals with psychiatric conditions leads to a notable reduction in the utilization of sleep medication. Patients diagnosed with SCZ often express a significant lack of understanding concerning proper sleep patterns, highlighting the potential necessity of applying a cognitive behavioral methodology when addressing insomnia within this population (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%